The Effect of Injury to Anterolateral Capsular Structures on Outcomes of ACL Injured Patients 24 Months after Anatomic ACL Reconstruction. Issue 3 (31st March 2017) - Azar, Amir Ata Rahnemai; Costello, Joanna; Popchak, Adam; Herbst, Elmar; Musahl, Volker; Tashman, Scott; Irrgang, James J.; Fu, Freddie H.
Objectives: The purpose of this study was to determine the effect of injury of anterolateral capsular structures (ALC) on outcomes of ACL injured patients 24 months after anatomic ACL reconstruction (ACLR). It was hypothesized that injury to ALC determined on Magnetic Resonance Imaging (MRI) scans would significantly affect patient reported outcomes (PROs) as well as in vivo joint kinematics during downhill running 24 months after ACLR. Methods: Subjects included a subset of ACL injured patients participating in a randomized clinical trial to compare single- and double bundle ACLR using quadriceps autograft. Subjects were divided into two groups based on the presence or absence of injury to ALC, as determined by a fellowship trained radiologist on Magnetic Resonance Imaging (MRI) scans performed within 6 weeks of injury (Kendall's tau-b for Inter-observer reliability = 0.75). ACLR outcomes were measured 24 months after surgery and included PROs (International Knee Documentation Committee Subjective Knee Form (IKDC-SKF) and Knee injury and Osteoarthritis Outcome Score (KOOS)) as well as in vivo joint kinematics during downhill running. In vivo joint kinematics were assessed while subjects performed downhill treadmill running (3.0 meters/second, 10° slope) within a Dynamic Stereo X-ray system (DSX). Knee kinematics were determined using a validated method for matching DSX images to tibiofemoral bone models obtained from subject specific computed tomography scans. A subset of joint kinematic variables (side-to-side differences for peak internal rotation, range of internal/external rotation, peak adduction and range of abduction/adduction) were evaluated in this study. These variables were selected based on the proposed function of the ALC for restraining internal knee rotation. The PROs and knee kinematics were compared between groups with and without ALC injury using independent t-tests. Statistical significance was set at p<0.05. Results: Thirty-five subjects (mean age: 22.8 ± 8.5 years) were enrolled in this study. The average interval between injury and performing the MRI scans was 9.5 ± 10 days. ALC injury was observed in 17 (48%) patients (grade 1: 6, grade 2: 10 and grade 3: 1). No differences were detected in PROs between groups with and without ALC injury (Figure 1 andTable 1 ). Likewise, no significant kinematic differences were found between groups. There was a slight trend towards greater external rotation in ACLR knees with ALC injury. Figure 1: Examples of (A) kinematics during downhill running (range of internal and external rotation) and (B) patient reported outcome (Internation Knee Documentation Committee Subjective Knee Form (IKDC-SKF)). No significant difference was observed between groups. Table 1: In vivo joint kinematics and patient reported outcome in patients with and without Anterolateral capsular structures (ALC) injury. No significant difference was observed. Variable No ALC injury mean (SD) ALC injury mean (SD) p -value In Vivo Joint Kinematics Peak Internal rotation (degrees) -0.29* (3.34) -1.94* (3.20) 0.18 Range of internal/external rotation (degrees) 3.03 (1.55) 2.73 (1.55) 0.6 Peak adduction (degrees) -0.56** (1.04) -0.79** (1.32) 0.61 Range of abduction/adduction (degrees) 0.96 (0.65) 0.94 (0.77) 0.95 Patient Reported Outcomes IKDC- SKF 91.59(10.74) 87.97 (11.18) 0.37 KOOS Symptoms 89.96 (7.52) 84.52 (11.10) 0.12 KOOS Pain 96.01 (6.49) 93.15 (13.56) 0.46 KOOS Function in Daily Living 99.17(2.08) 96.86 (11.35) 0.43 KOOS Function in Sports and Recreation 91.56(13.00) 90.33 (11.72) 0.79 KOOS Knee Related Quality of Life 88.67(17.26) 77.50 (24.75) 0.15 *Negative value denotes external rotation ** Negative value denotes abduction Conclusion: The most significant finding of this study was that combined injury to ALC did not significantly affect PROs or knee kinematics 24 months post ACLR. Based on these findings, performing additional reconstruction/repair surgery to reduce excess rotational laxity due to presence of ALC injury is not supported. Accordingly, it is recommended to observe MRI detectable injuries to the ALC.